Development of the DASHY-25M Teaching Aid Design at the Department of Mechanical Engineering, Politeknik Kuching Sarawak - Hamzah, Haizal Mohd; Gazi, Suhana Binti Mohd; Halit, Yusmi Bin; Saeman, Muhadir Bin (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This research details the development and evaluation of the DASHY-25M, a physical teaching aid designed to enhance the efficacy of teaching and learning (T&L) methodologies in mechanical engineering education, specifically in design-focused courses such as Computer-Aided Design (CAD). Background Problems: Conventional pedagogical approaches in mechanical engineering often struggle to bridge the gap between digital simulation and physical reality. Instruction that relies exclusively on theoretical lectures and software-based exercises can constrain student comprehension by lacking a tangible, hands-on component. Novelty: The novelty of this study lies in the DASHY-25M itself—a physical teaching aid developed to provide a complementary, hands-on learning modality aimed at enhancing students’ understanding of complex design principles and their real-world manufacturing and assembly applications. Research Methods:This study employs a quantitative, descriptive-correlational approach. Data will be collected via a questionnaire distributed to approximately 200 mechanical engineering diploma students at Politeknik Kuching Sarawak and analyzed using descriptive and inferential statistics to assess the aid’s impact on student comprehension and perception. Finding/Results: As the study is presented in a proposal format, specific empirical findings are not yet available. The hypothesis states that the integration of the physical aid is expected to show a significant positive correlation with students’ conceptual understanding and practical skills. Conclusion: It is anticipated that the integration of the DASHY-25M will address a critical gap in current pedagogical practice by strengthening the link between digital design theory and physical application, thereby enhancing learning outcomes in mechanical engineering education.